The Nexus between Data, Information and Knowledge during the COVID-19 Pandemic: Navigating the Knowledge Management Landscape in South Africa - Garaba, Francis; Nawe, Takatso (Mousaion: South African Journal of Information Studies, 2022)
This viewpoint paper is based on desktop research focusing on the discourse of knowledge management (KM). We explore the situation in South Africa with reference to this global COVID-19 apocalypse that the world is being confronted with. By using a qualitative research approach, the concepts of data, information and knowledge are unpacked in the context of this pandemic. KM is evident in the creation, storing, using and effective sharing of information and knowledge in light of COVID-19. The sharing and dissemination of information are, however, technologically orientated as advances in this realm continue to elevate opportunities for transforming KM. All information that has been created and is available to inform society about the virus is shared and distributed through technological means such as electronic and print media, the Internet and social media. As people adjust to the new normal, they will have a hefty repository of pandemic stories, enriched with new vocabulary about the virus and centred on the three concepts of data, information and knowledge. Understanding this new terminology plays a key role in helping to prevent the spread of COVID-19. Incorrect use of this vocabulary can lead to misinformation and could endanger the lives of others. Both the public and government now need “moral knowledge” about the pandemic in the fight against this virus.